Изучение свойств кальцийсодержащего материала, применяемого для лечения хронического периодонтита (Эндодонтия Today, 2020)
The article is devoted to the application of well-known calcium-containing material of Vitapex produced by Neo Dental Chemical Company (Japan). The publication presents the results of the study of microbiological, physical and chemical properties of the material. Noted the lack of antibacterial effect, the high apical permeability of the material.